THE IMPACT OF THE IMPLEMENTATION OF THE MINISTRY OF RELIGION'S POLICY ON THE COMPETENCE OF ISLAMIC TEACHERS IN NORTH SUMATRA - Nurhaizan Sembiring (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study aims to analyze the impact of the implementation of the Ministry of Religion's policies on the competence of Islamic religious teachers in North Sumatra. The research uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observations, and documentation studies. The research informants included Islamic religious teachers, madrasah supervisors, and officials of the local Ministry of Religion who were selected purposively. The results of the study show that the policies of the Ministry of Religion, such as certification, Teacher Professional Education (PPG), and religious moderation training, have a positive impact on improving teacher competence, especially in pedagogic and professional aspects. Teachers who participate in PPG are able to develop innovative learning methods and master teaching tools better, while certification increases motivation and well-being. In the personality and social aspects, policies encourage teachers to be role models and instill the value of tolerance. However, policy implementation is not evenly distributed, especially in rural areas that face limited facilities, access to information, and bureaucracy. This study concludes that the Ministry of Religion's policies contribute significantly to improving the competence of Islamic religious teachers, but it is necessary to have equal access and strengthen infrastructure to be more optimal.